Influence of fish oil in the concentration of conjugated linoleic acid and omega 6 and 3 in buffalo milk - Patiño, Exequiel María (2012)
The aim of this research work was to investigate the influence of fish oil supplementation on the concentration of conjugated linoleic acid (CLA) and omega 6 and 3 in samples of buffalo milk. A total of 24 female buffaloes separated at random into three groups were fed for 49 days with: natural pasture (group I), supplemented with 70mL of fish oil (group II) and 140mL of fish oil (group III). In the experiment the concentration of CLA showed differences (P0.05) among the three groups, with a maximum of 7.14mg/g fat in group II. No significant differences were found in omega-6 among the three groups. The highest value of 3.82mg/g fat corresponded to group I, whicht had not been supplemented with fish oil. Significant differences were observed in omega 3 (P0.05) in groups II and III with respect to group I. The highest average value of 2.42mg/g fat was obtained in group III. The closest relationship omega 6/3 (1.37:1) was observed in group III. As a result, the diets of groups II and III, which included fish oil, increased significantly the content of CLA and omega 3 with reductions in levels of omega 6.